Tau protein squired by molecular chaperones during alzheimer's disease - Gorantla, Nalini Vijay; Chinnathambi, Subashchandrabose (Journal of Molecular Neuroscience, 2018)
Alzheimer's disease (AD) is a neurodegenerative disorder characterized by progressive neuronal loss, caused by misfolding and accumulation of tau and Amyloid -42. Cellular mechanisms involving phosphatases, chaperones, ubiquitin proteasome system (UPS) and aggresomes solubilize or remove these toxic aggregates. Chaperones such as Hsp70 and Hsp90 functions in folding tau to its native form or in the downstream degrade and eliminated tau from the cell. Chaperones are involved in lysosomal degradation of tau by a process called chaperone mediated autophagy (CMA). In pathological conditions, chaperones fail to remove the toxic tau species, leading to their accumulation. In this scenario, inhibiting the chaperone activity would aid in overcoming AD. Small molecules inhibitors against chaperone activity are known to be effective in the clearance of aberrant tau from cell. In this review, the aspects of inhibition and prevention of tau aggregates formation are discussed in terms of chaperone activity and their small molecule modulators.

Transition metal nickel prevents Tau aggregation in Alzheimer's disease - Gorantla, Nalini Vijay; Das, Rashmi; Balaraman, Ekambaram; Chinnathambi, Subashchandrabose (International Journal of Biological Macromolecules, 2020)
Alzheimer's disease is the leading cause of dementia, effecting majority of aged people worldwide. The multifaceted effectors of Alzheimer's disease primarily include Tau, amyloid-beta along with hyper activation of kinases, oxidative stress and mutations etc., makes it challenging to design therapeutics. Tau is a microtubule-associating protein, which is subjected to cellular stress resulting in the formation of neurofibrillary tangles, leading to loss of affinity for microtubules. This causes loss of microtubule stability and in turn alters axonal integrity. In the present work, emphasis towards understanding interaction of nickel with Tau was made. Metals such as iron, zinc, copper and lead etc., are known to modulate Tau conformation and enhance its aggregation. Our results showed the deliverance of Tau aggregation by nickel and its synthetic morpholine conjugate. Nickel prevents aggregation by inducing degradation of Tau as evidenced by SDS-PAGE and TEM. Nickel and the synthetic conjugate being non toxic to neuro2a cells and prevent Tau aggregation, might direct these complexes to overcome AD. (C) 2019 Published by Elsevier B.V.
Keywords: Aggregation; Alzheimer's disease; metals; Morpholine; Nickel chloride; Tau